Spontaneous malformations of the cerebellar vermis: Prevalence, inheritance, and relationship to lobule/fissure organization in the C57BL/6 lineage. (3rd December 2015) - Van Dine, S.E.; Siu, N.Y.; Toia, A.; Cuoco, J.A.; Betz, A.J.; Bolivar, V.J.; Torres, G.; Ramos, R.L.
Highlights: Malformation of the vermis is a heritable and recessive trait. Inbred mice exhibit variation in the pattern of cerebellar folia. Malformation of the vermis is unrelated to folia patterning. Abstract: The complex neuronal circuitry of the cerebellum is embedded within its lamina, folia, and lobules, which together play an important role in sensory and motor function. Studies in mouse models have demonstrated that both cerebellar lamination and lobule/fissure development are under genetic control. The cerebellar vermis of C57BL/6 mice exhibits spontaneous malformations of neuronal migration of posterior lobules (VIII–IX; molecular layer heterotopia); however, the extent to which other inbred mice also exhibit these malformations is unknown. Using seven different inbred mouse strains and two first filial generation (F1) hybrids, we show that only the C57BL/6 strain exhibits heterotopia. Furthermore, we observed heterotopia in consomic and recombinant inbred strains. These data indicate that heterotopia formation is a weakly penetrant trait requiring homozygosity of one or more C57BL/6 alleles outside of chromosome 1 and the sex chromosomes. Additional morphological analyses showed no relationship between heterotopia formation and other features of lobule/fissure organization. These data are relevant toward understanding normal cerebellar development and disorders affecting cerebellar foliation and lamination.